Program and abstracts of the 51st annual meeting of the American Society of Tropical Medicine and Hygiene (American Society of Tropical Medicine and Hygiene, 2002)
The publication contains the program and abstracts of a conference that focused on tropical medicine and hygiene. Intended for professional public.
American journal of tropical medicine and hygiene, ISSN 0002-9637 Volume 67, number 2, supplementum August 2002
Keywords: Hygiene; Tropical Medicine; hygiena; kongresy jako téma; tropické lékařství; Congresses as Topic; cestovní a tropická medicína